Identification of oral bacterial species associated with halitosis - Haraszthy, Violet I; Zambon, Joseph J; Sreenivasan, Prem K; Zambon, Margaret M; Gerber, Doralee; Rego, Rodrigo; Parker, Carol (The Journal of the American Dental Association (1939), 2007)
The authors examined the tongue bacteria associated with oral halitosis (bad breath originating from the oral cavity), focusing on noncultivable bacteria-bacteria that cannot be identified by bacterial culture techniques. The authors took samples from the dorsal tongue surface of eight adult subjects with halitosis and five control subjects who did not have halitosis. They identified the bacteria in these samples by using both anaerobic culture and direct amplification of 16S ribosomal DNA, a method that can identify both cultivable and noncultivable microorganisms. They analyzed the resulting microbiological data using chi(2) and correlation coefficient tests. Clinical measures of halitosis were correlated highly with each other and with tongue coating scores. Of 4,088 isolates and phylotypes identified from the 13 subjects, 32 species including 13 noncultivable species were found only in subjects with halitosis. Solobacterium moorei was present in all subjects with halitosis but not in any control subjects. Subjects with halitosis harbor some bacterial species on their dorsal tongue surfaces that are distinct from bacterial species found in control subjects. This finding is consistent with the hypothesis that halitosis has a microbial etiology. Like other oral diseases with microbial etiology, halitosis may be amenable to specific and nonspecific antimicrobial therapy targeted toward the bacteria associated with it.